Perspectives of forest management planning : Slovenian and Croatian experience - Bončina, Andrej (Array, 2009)
Summary: Drawing upon the historical framework of origin and development, and a long tradition in forest management planning in Slovenia and Croatia, and based on a survey of literature and research to date, this paper addresses problems and perspectives of forest management planning. Comparison is made of forest management planning concepts, which generally differ from country to country in terms of natural, social and economic circumstances. Impacts of forest management planning on the condition and trends in forest resources are discussed. Perspectives of forest planning and management are viewed as a permanent and continuous task. This task involves sustainable forest management through the development of integral and close-to-nature management.Within the adaptive approach to management as the main focus of future planning development, the core elements of forest management planning are discussed: planning as a process, inventory and planning, project planning and design, team work, importance of management monitoring and analyses, spatial levels of planning, and finally, creativity and restrictions of adaptive management. Involvement of the public and of all interested subjects in the forest management planning process is highlighted as an essential prerequisite for developing a planning approach, and so is the establishment of an efficient system of private forest management planning and entrepreneurship